2021
DOI: 10.1038/s41388-021-01952-w
|View full text |Cite
|
Sign up to set email alerts
|

AML1/ETO and its function as a regulator of gene transcription via epigenetic mechanisms

Abstract: The chromosomal translocation t(8;21) and the resulting oncofusion gene AML1/ETO have long served as a prototypical genetic lesion to model and understand leukemogenesis. In this review, we describe the wide-ranging role of AML1/ETO in AML leukemogenesis, with a particular focus on the aberrant epigenetic regulation of gene transcription driven by this AML-defining mutation. We begin by analyzing how structural changes secondary to distinct genomic breakpoints and splice changes, as well as posttranscriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 137 publications
1
22
0
Order By: Relevance
“…The addition of capture sequence to the gRNA backbone enabled their detection coincidentally with the single-cell transcriptome and this allowed us to demonstrate that that RUNX1T1 gRNAs were significantly enriched in cells within the expanded arterial cluster. RUNX1T1, also known as ETO, has been associated with the t(8;21) chromosomal translocation that results in the generation of the leukemic fusion protein, AML1/ETO (Rejeski, Duque-Afonso and Lübbert, 2021). RUNX1T1 expression has been recently detected in transcriptomic analysis of the human AGM region (Zeng et al ., 2019; Calvanese et al ., 2022), but its precise role during the ontogeny of the blood system has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of capture sequence to the gRNA backbone enabled their detection coincidentally with the single-cell transcriptome and this allowed us to demonstrate that that RUNX1T1 gRNAs were significantly enriched in cells within the expanded arterial cluster. RUNX1T1, also known as ETO, has been associated with the t(8;21) chromosomal translocation that results in the generation of the leukemic fusion protein, AML1/ETO (Rejeski, Duque-Afonso and Lübbert, 2021). RUNX1T1 expression has been recently detected in transcriptomic analysis of the human AGM region (Zeng et al ., 2019; Calvanese et al ., 2022), but its precise role during the ontogeny of the blood system has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, aberrant chromosomal translocations can generate gene fusions, producing oncofusion proteins which underpin tumorigenesis. One of the most widely detected oncofusion genes, AML1-ETO (AE), is widely known to be responsible for myeloid leukemogenesis [ 100 , 101 , 102 ]. Shima et al (2019) showed that the AE fusion gene consists of four canonical PASs and favors a shorter length in both t(8;21) AML primary patients and cell lines [ 103 ].…”
Section: 3’ Untranslated Regions (3’utrs) Of Mrnasmentioning
confidence: 99%
“…The AML1-ETO protein is viewed as regulating gene expression via epigenetic mechanisms. The fusion protein recruits multiple chromatin-modifying enzymes to target genes, to alter chromatin marks and transcription factor binding ( Rejeski et al, 2021 ). The MLL1 gene that is rearranged in infant B-cell ALL encodes the histone lysine-specific methyltransferase 2A which plays a role in gene expression ( Winters and Bernt, 2017 ).…”
Section: Signature Mutations In Leukemiamentioning
confidence: 99%